(untitled) (Homoeopathy for All, 2024)
Psychosomatic diseases which are also called as psychological Factors that affect Physical condition by DSM-V. These are the conditions by where psychological factors (stress, anxiety) triggered or exacerbated physical illnesses. Stress has a strong influence on mind and emotions thereby affect the functioning of mind and physical body. The article shows how Homoeopathic approach is best for psychosomatic diseases, how the principle of homoeopathy helps in understanding the psychosomatic diseases because when homoeopathy cures a normal individual, the deeper side of his being i.e., emotions, the will and the understanding or the rational mind comes into equilibrium i.e., health